The Strategic Framework of Cost Management for Production Competitiveness: World Experience - Dubovaya, Valentina; Komelina, Anna; Hassan Ismail, Shamila (International Journal of Engineering and Technology, 2018)
Purpose of the article is to analyze the concept of production competitiveness and develop framework of cost management. A variety of cost management techniques requires the identification of their relationship with the requirements of operations management. Identified seven key concepts of operations management, analyzed their essence, information requirements. Systematized cost management techniques accordance with modern concepts of operations management such as: standart-costing, break-even analysis, direct-costing, life-cycle costing, target costing, value analysis, functional analysis, activity-based costing, sensitivity analysis, JIT-costing, kaizen costing, activity-based cost management, value-chain analysis. The aim of the article is the establishment relevance of costing methods with the key concepts of operations management companies.Â Â